Strategi Dinas Tenaga Kerja dan Transmigrasi Kabupaten Bengkalis dalam Mengurangi Pengangguran di Kota Duri - Ainun Mardiah; Rizma Alfiyati; Sehani Sehani (PUBLICNESS: Journal of Public Administration studies, 2022)
This research was conducted at the Department of Manpower and Transmigration of Bengkalis Regency. This study aims to analyze the strategy of the Manpower and Transmigration Office of Bengkalis Regency in reducing unemployment in Duri City and to find out what are the obstacles to the Bengkalis Regency Manpower and Transmigration Office in reducing unemployment in Duri City. The research method used descriptive qualitative by using several data collection techniques, namely interviews with research informants, observation and also documentation. The results of the study revealed that the strategy of the Bengkalis Regency Manpower and Transmigration Office in carrying out the strategy program was assessed from the previous year as being maximal, except that in 2020 it was not maximized. It can be seen from the unemployment data which is still increasing in 2020. The obstacles to implementing the strategy in reducing the unemployment rate in this city of thorns are the limited budget and there are still many non-functional human resources.